2021
DOI: 10.1007/978-3-030-69221-6_57
|View full text |Cite
|
Sign up to set email alerts
|

FinTech in Bahrain: The Role of FinTech in Empowering Women

Abstract: The purpose of this paper is to review the definition of Financial Technology (FinTech) discipline from different perspectives and scholars. Moreover, the research will explore FinTech history and its evolution stages throughout the years based on existing literatures. In addition, it will present the different concepts and categories of FinTech. The research will also discuss FinTech implementation in the Kingdom of Bahrain and focus on women role within the FinTech, and the initiatives taken to em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Although Kingdom of Bahrain has also shown interest by encouraging its population especially women to follow FinTech-driven applications. 50,114…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Kingdom of Bahrain has also shown interest by encouraging its population especially women to follow FinTech-driven applications. 50,114…”
Section: Resultsmentioning
confidence: 99%
“…Although Kingdom of Bahrain has also shown interest by encouraging its population especially women to follow FinTech-driven applications. 50,114 From the extant it is concluded that a lot of research work must be carried on from this region (GCC) by introducing a Blockchain driven, and venture capitalist facilitated ecosystem. This research work will help in: What are the social impacts of FinTech on the GCC region?…”
Section: Sensitive Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…AI is defined as a machine's ability to learn, analyze, and comprehend information in a manner comparable to that of humans (Tamzid, 2021). The emergence of various concepts like e-government, e-governance, information systems, e-Health, and so forth was facilitated by the development of technology in various fields (Alshaikh et al, 2017;Mohamed et al, 2021;Razzaque et al, 2013;Razzaque & Karolak, 2010). In the world of business, the impact of technology has become also prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…Although the idea of financial technology (FinTech) is not new (Mohamed et al, 2021), according to some, a new era is beginning as a result of the rise and the most recent evolution of fintech. financial sector, and innovation are all connected by the term "fintech".…”
Section: Introductionmentioning
confidence: 99%